2015
DOI: 10.1186/s12955-015-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its association with direct medical costs for COPD in urban China

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. Few studies have focused on the quality of life (QoL) associated medical costs for COPD in China.MethodsA cross-sectional survey of 678 COPD patients was conducted in four major cities (Beijing, Shanghai, Guangzhou and Chengdu), China, in 2011. Data on socio-demographic information, health conditions and medical costs were collected through a face-to-face interview combined with medical record searching. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 29 publications
2
31
1
3
Order By: Relevance
“…This study has presented evidence of the financial and quality‐of‐life costs to people who have chronic wounds. A further consideration is the relationship between financial cost and quality of life given that research conducted with people who have other chronic conditions, such as COPD and Alzheimer's disease , has shown that poorer quality of life can be associated with higher medical health care costs. It is suggested that increased use of services, associated with better quality of life and help seeking behaviours, is accountable for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…This study has presented evidence of the financial and quality‐of‐life costs to people who have chronic wounds. A further consideration is the relationship between financial cost and quality of life given that research conducted with people who have other chronic conditions, such as COPD and Alzheimer's disease , has shown that poorer quality of life can be associated with higher medical health care costs. It is suggested that increased use of services, associated with better quality of life and help seeking behaviours, is accountable for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 721 COPD patients were invited and 94% of them were eligible based on the inclusion criteria (local residents who lived in the city for at least 2 years without any unstable comorbidities or any severe conditions needed to be treated as inpatients). COPD cases who did not meet the inclusion criteria were excluded 12. A written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…There is no cure for COPD, therefore, the purpose of pharmacological and nonpharmacologic treatments is to mitigate symptoms and improve quality of life [1,2]. Therefore, the healthrelated quality of life (HRQoL) of patients with COPD has been considered an important disease outcome in recent clinical studies [3,4]. Tools assessing HRQoL should be able to differentiate it according to the patient's clinical status [5].…”
Section: Introductionmentioning
confidence: 99%